2004
DOI: 10.1002/ijc.20672
|View full text |Cite
|
Sign up to set email alerts
|

Screening for family members of patients with nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is well known for its peculiarly skewed distribution with highest incidence in Southern Chinese population. Familial aggregation is evident, hence screening for early detection is offered by oncology centers in Hong Kong to first-degree relatives of patients with NPC. During the period 1994 -2001, 929 family members were screened in our center. The screenees were advised to attend an annual examination that includes serological test against Epstein Barr Virus (EBV), physical exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 15 publications
1
48
2
1
Order By: Relevance
“…1 Although several previous studies [2][3][4][5] have reported on the use of EBV serology for screening and early detection of NPC, the role of EBV DNA detection as a screening test for NPC remains to be defined. Circulating cell-free EBV DNA is detectable in the plasma of 96% of NPC patients 6 by quantitative real-time polymerase chain reaction (PCR) and has been shown to be a useful marker in prognostication 7 as well as residual disease detection.…”
Section: Dear Sirmentioning
confidence: 99%
“…1 Although several previous studies [2][3][4][5] have reported on the use of EBV serology for screening and early detection of NPC, the role of EBV DNA detection as a screening test for NPC remains to be defined. Circulating cell-free EBV DNA is detectable in the plasma of 96% of NPC patients 6 by quantitative real-time polymerase chain reaction (PCR) and has been shown to be a useful marker in prognostication 7 as well as residual disease detection.…”
Section: Dear Sirmentioning
confidence: 99%
“…Its highest incidence is in the Southern Chinese population, with familial aggregation. The annual detection rate is 433 per 100,000 for men and 499 per 100,000 for women in high-risk families, as compared with an average overall annual incidence in Hong Kong of 24 per 100,000 for men and 10 per 100,000 for women 171 .…”
Section: Prevention Of Cancer Progressionmentioning
confidence: 96%
“…Further genetic and epigenetic alterations post-NPC development can occur, which may result in a more metastatic disease. Because of it takes years for premalignant lesion after EBV infection to NPC formation (Choi et al, 2011;Ji et al, 2007;Ng et al, 2010;Ng et al, 2005), the long period of pre-clinical detectable phase (PCDP) offer the opportunity for screening and early diagnosis of NPC.…”
Section: Ebv Related Pathogenesis Of Npcmentioning
confidence: 99%
“…Screening in Hong-Kong with positive NPC family history was conducted since 1994 Ng et al, 2010;Ng et al, 2005). Participants in this screening program for NPC were all first degree relatives of patients with NPC and they were all 18 years of age or older.…”
Section: Screening In High Risk Group With Positive Family Historymentioning
confidence: 99%